The Impact of Takaful Insurance on the Manufacturing Industry in Malaysia: Empirical Evidence through ARDL Bounds Testing Approach - Achmakou Lahoucine (European Scientific Journal, ESJ, 2023)
In post-financial crisis, the interconnection between the financial sector and real activity is gaining more interest in the literature. Given that the insurance sector represents a large part of the financial globe, it will be essential to explore its impact on the real economy. Further, the expansion of participative finance, in the last decade, requires contextualising the question in this sense. However, this paper experiments with the effect of Takaful insurance on real activity in Malaysia. Hence, an ARDL model is estimated on quarterly data between 2010Q1 and 2017Q4. The results show a positive and significant impact of the increase in Takaful contributions to manufacturing activity. On the same side, a long-term relationship between the two sides is established in the image of a significative cointegration.